Phenotypic constraints at the top of the world: an Arctic songbird faces the cumulative cost of maintaining a winter-like phenotype during breeding - Le Pogam, Audrey; O’Connor, Ryan S.; Love, Oliver P.; Young, Kevin G.; Drolet, Justine; Régimbald, Lyette; Roy, Gabrielle; Robitaille, Francis; Berteaux, Dominique; Tam, Andrew; Vézina, François (Frontiers in Ecology and Evolution, 2024)
Among birds, several body composition traits typically decrease in size or mass during breeding likely as a result of competing demands during this critical life history stage. However, a recent outdoor captive study in an Arctic-breeding cold-specialist songbird (snow buntings -Plectrophenax nivalis) demonstrated that these birds maintain winter cold acclimatization during the spring and summer, despite facing summer temperatures much warmer than on their Arctic breeding grounds. This suggests that buntings may face a cumulative physiological cost during breeding: having to support a winter phenotype while also upregulating additional traits for reproduction. The current study aimed to test this hypothesis. Between 2016 and 2019, we examined how body composition and metabolic performance (thermogenic capacity and physiological maintenance costs) changed from pre-breeding to chick provisioning in free-living birds captured at the northern limit of their breeding range in the Canadian Arctic (Alert, NU, 82°). While body mass and fat reserves deceased significantly between pre-breeding and territory defense independent of thermal conditions, cold endurance and associated traits remained stable and elevated up to the nestling provisioning period, as long as ambient temperature remained below a threshold level of 0-2°C. These results indicate that snow buntings must maintain a high thermogenic capacity after arrival on the breeding grounds if temperatures remain below freezing, regardless of whether birds are actively breeding or not. In this context, our research suggests that these birds, and possibly other arctic breeding songbirds, may experience cumulative physiological costs during years with a late onset of spring, when breeding activities (i.e., egg production and incubation) begin while temperatures are still below 0-2°C.